El papel de la Bahía de Mazarrón (Murcia) en los contactos comerciales mediterráneos en época romana - Modrzewska-Pianetti, Iwona (Rome and Iberia : Inspirations and Connections throughout History, 2021)
For many years I have dedicated myself to the study of commercial contacts between the Roman provinces, based on research on amphorae. The knowledge of the production of the amphorae of Baetica and the deposits of the amphorae of Galia Cisalpina made it possible to draw conclusions about commercial contacts between these provinces. The aim of my new study of amphorae from Mazarrón Bay (Murcia), funded by the NCN - National Science Centre in Poland, arose from my previous research. Thanks to the collaboration of the University of Murcia, the Archaeological Museum of Murcia and the Municipal Archaeological Museum of the “Factoría Romana de Salazones” of Mazarrón, I was able to document the hitherto unpublished amphorae of the Mazarrón coast. During the process of documenting 574 amphorae, excavated in the dredging works in Puerto de Mazarrón, in the stores of the Museum of Murcia and the Museum of Mazarrón, I registered 169 containers coming from the production of the south coast of the region of Murcia. The typological and chronological elaboration, as well as the comparison with the finds of amphorae in the interior of the Mazarrón area, allow conclusions to be drawn about the local production and imports of containers from other regions of the Iberian Peninsula and from other Mediterranean areas. The study, based on pieces of material culture, allows the reconstruction of the role of Mazarrón Bay in the ancient trade of the peninsular southeast and other Mediterranean areas.